Content Knowledge on the Highlights of the K to 12 Curriculum Implementation: Basic for a Proposed Development Plan - R. Carreon, Joseph (ASEAN Journal of Education, 2023)
Teachers as a steward for cognizant transformational change must continuously upgrade their personal growth and professional development. The need to optimize competency-based teacher standards in order to carry out a high performance of their roles and responsibilities as a key to realize the imperatives of the K to 12 curriculum program brings focus in this study. The study assess the content knowledge on the highlights of the K to 12 curriculum implementation of the Technology and Livelihood Education (TLE) teachers of General Emilio Aguinaldo National High School. The study was purposively involved 31 teachers using the descriptive-quantitative research design with the support of the focus group discussion. A validated researcher-made questionnaire with corresponding arbitrary scale and verbal interpretation was used in the study. The findings of the study revealed that only 71 % were able to attend K to 12 seminars/training, 52 % have a Master degree, 3 % have a Ph.D. and 45 % are less than three years in service. It was also revealed that teachers had a satisfactory level of content knowledge on the pre-assessment with a mean of 3.08 or 77 % indicative level of awareness. The in-service training program through capacity building highly improved teacher’s content knowledge with a mean of 3.79 or 94.75 % indicative level of awareness. Thus, the in-service training program that responds to teachers’ competency needs standards was deemed effective in intensifying content knowledge of the TLE teachers of the current development in education. The study suggests to sustain the proposed development plan in initiating seminar, training, and assessment regardless of curriculum reform to further upgrade teacher’s competence.